Thermodynamic and environmental comparative analysis of a dual loop ORC and Kalina as bottoming cycle of a solar Brayton sCO2 - José Manuel Tovar; Guillermo Valencia Ochoa; Daniel Mendoza Casseres (International Journal of Thermofluids)
Solar energy as a thermal source has become a viable and thermo-sustainable option to generate heat, for the energy production through power cycle configurations. In this article, the balances and application of life cycle analysis (LCA) allowed to proposed thermodynamic models in order to conduct a comparative study of the energy, exergy and environmental performance of two hybrid power generation systems using a supercritical carbon dioxide Brayton with recompression, intercooling and reheating (sCO2) as the main cycle coupled to two waste heat recovery technologies: dual loop Rankine organic cycle (DORC) and Kalina cycle (KC). The results showed that the Brayton sCO2/DORC configuration presented better exergetic performance using Toluene (23.98%), Cyclohexane (24.01%), and Acetone (24.06%) as working fluids concerning the Brayton sCO2/KC configuration with a 23.82%. In addition, the solar field was the component with the highest irreversibility rate (∼61.6%) when the system operated at 100% solar energy. In terms of environmental impact, the results indicate that the concentrating solar power (CSP) tower is the device that generates the most emissions in the systems studied (∼90%). Acetone was found to be 36% more polluting than the working fluid used in the sCO2/KC system (Ammonia). In addition, aluminum as a construction material emits 5.26 % more kg CO2-equi than steel in both systems. Also, the construction phase is the LCA stage that has the greatest impact, representing approximately 95.4% of the total emissions, followed by the decommissioning phase (4.5%) and operation (0.05%). These results show good thermo-sustainable performances that in conjunction with thermo-economic optimizations could achieve solutions applicable to the local industrial sector.